Local Leadership in Implementing Public Digital Transformation towards Deli Serdang Smart City - Pardede, Piki Darma Kristian; Panjaitan, Doli Tua Mulia Raja; Perwirawati, Elok (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
One of the challenges in encouraging digital transformation within local government is the commitment to developing a comprehensive digital ecosystem. This study aims to see how local leadership can integrate Smart City Policy in transforming regional government governance to be more efficient and fairer. This research is qualitative based with a descriptive approach. The research results show that digital transformation in the Deli Serdang Regency Government has yet to impact the smart city's main goals. The Smart City concept is no longer limited to just ICT diffusion, city leaders must innovate in core service areas in implementing the Smart City concept. However, there is still a silo mentality in regional apparatus organizations, which is shown by the resistance and rejection of e-gov, which is triggered by a lack of awareness and appreciation for e-gov, and unwillingness to share data and information, thus causing inefficient information flow to support public service performance. There is a need to incorporate knowledge of social values and unique institutional arrangements by encouraging partnership synergy in utilizing local leaders' resources and capacities in smart city implementation. Local leaders must restructure and act in line with core public values and combine the values of digitalization with a democratic context to achieve a prosperous society that prioritizes equality and participation.